Integral bridge abutments in response to seasonal temperature changes: State of knowledge and recent advances - Liu, Hao; Han, Jie; Parsons, Robert L. (Frontiers in Built Environment, 2022)
Expansion and contraction of integral abutment bridges due to temperature changes force integral bridge abutments (IBAs) to move toward and away from the backfill, thus increasing horizontal earth pressures behind the abutments and inducing bending moments on pile foundations. This paper presents the state of knowledge and recent advances in understanding the behavior of IBAs in response to temperature changes including abutment movement, pile response, and horizontal earth pressure behind the abutment, examines the effect of bridge skew on the behavior, and discusses possible measures to mitigate temperature change-induced problems for IBAs. Field data show that both bending moments of piles near the bottom of abutments and axial loads of piles fluctuated with temperature. Redistribution of dead loads among bridge components due to planar temperature gradients and earth pressure changes behind the abutment contributed to axial load fluctuations in piles. Magnitude and distribution of horizontal earth pressures behind the abutment depend on factors such as abutment movement and abutment movement mode. Most of the current design methods overestimated the horizontal earth pressures at the bottom of the abutment during bridge expansion. Compressible inclusions placed behind the abutment, geosynthetic-reinforced backfill, and lightweight backfill in place of typical aggregate backfill are helpful to reduce horizontal earth pressures behind the abutment at high temperatures and temperature change-induced backfill settlements.